Red Clay as a Raw Material for Sustainable Masonry Composite Ceramic Blocks - Samardzioska, Todorka; Peshevski, Igor; Zileska Pancovska, Valentina; Golaboski, Bojan; Jovanovski, Milorad; Abazi, Sead (MDPI AG, 2025)
The pursuit of sustainable construction practices has become imperative in the modern era. This paper delves into the research of the properties and application of a specific material called “red clay” from the locality “Crvena Mogila” in Macedonia. A series of laboratory tests were conducted to evaluate the physical, mechanical, and chemical properties of the material. The tested samples show that it is a porous material with low density, high water absorption, and compressive strength in range of 29.85–38.32 MPa. Samples of composite wall blocks were made with partial replacement of natural aggregate with red clay aggregate. Two types of blocks were produced with dimensions of 390 × 190 × 190 mm, with five and six holes. The average compressive strength of the blocks ranges from 3.1 to 4.1 MPa, which depends on net density and the number of holes. Testing showed that these blocks have nearly seven-times-lower thermal conductivity than conventional concrete blocks and nearly twice-lower conductivity than full-fired clay bricks. The general conclusion is that the tested red clay is an economically viable and sustainable material with favourable physical, mechanical, and thermal parameters and can be used as a granular aggregate in the production of composite ceramic blocks.